One more eraption an analysis of selected television interviews of Joseph Estrada as candidate for City Mayor in Manila in the 2013 local elections - Valdeavilla, Ronica L. 1992- (2013)
"This qualitative study aimed to identify how Joseph Estrada communicates with the Filipino audiences and how the media portrays him through his television interviews as a candidate for City Mayor of Manila. The Rhetorical Theory and the second level of Agenda Setting Theory of Communication were the theories used in the study. Also, the researcher used discourse analysis and thematic analysis to analyze seven selected television interviews of Estrada from April 2012- January 2013. Seven recurring themes were identified in the study. The findings of the study reveal that Estrada invokes a set of rhetorical appeal, namely, ethos, pathos and logos when communication. It was also found out that Estrada was portrayed in the television interviews as a formidable candidate for City Mayor of Manila in the May 2013 elections."